PigSmart Uganda- Your reference booklet on piggery - International Livestock Research Institute (International Livestock Research Institute, 2025)
Keeping pigs is an excellent way for farmers to make money and feed their families. But while pigs are known for being easy to raise, you still need to practice good animal welfare and farm management.